2011
DOI: 10.1007/s13197-011-0472-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing parameters on fouling resistances during microfiltration of red plum and watermelon juices: a comparative study

Abstract: This study evaluated the total (R t ), reversible (R rev ), irreversible (R irr ), and cake (R c ) resistances during microfiltration of watermelon juice (as a juice with colloid particles) and red plum juice (as a juice without colloid particles). Results showed that the total resistance decreased by about 45% when the feed velocity was increased during clarification of red plum juice due to change in cake resistance. Also, increasing the feed temperature from 20 to 30°C decreased the total fouling resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Again pure water flux of cleaned membrane (Jw) was calculated. The fouling factor ( F ) of membrane can be calculated using the following equations (Cassano et al ., ; Juang et al ., ; Nourbakhsh et al ., ,b): Jnormalw=QA.ΔTJnormalw=ΔPnormalμnormalwRR=Rm+Rf%F=JwJwJnormalw×100…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Again pure water flux of cleaned membrane (Jw) was calculated. The fouling factor ( F ) of membrane can be calculated using the following equations (Cassano et al ., ; Juang et al ., ; Nourbakhsh et al ., ,b): Jnormalw=QA.ΔTJnormalw=ΔPnormalμnormalwRR=Rm+Rf%F=JwJwJnormalw×100…”
Section: Resultsmentioning
confidence: 97%
“…The variation in ω3‐PUFA concentration due to change in stirring rate can be related to the fouling factor. To calculate the fouling created due to oil transport in ETNA01PP, the pure water flux ( J w ) through membrane was calculated according to eqn , and by equalling the eqns and , the membrane resistance was calculated (Cassano et al ., ; Juang et al ., ; Nourbakhsh et al ., ,b). Jnormalw=QA.ΔTJnormalw=ΔPnormalμnormalwRnormalm, where J w is the pure water flux (L m −2 h), Q is the quantity of the water permeate (L), A is the membrane area (m 2 ), Δt is the sampling time (h), ΔP is feed pressure (Pa), μ w is water viscosity (Pa.s), and R m is membrane resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nourbakhsh et al . () studied the microfiltration of watermelon juice in a cross‐flow membrane system and demonstrated that the total resistance to permeation flux decreased by approximately 54% when feed temperature was increased from 20 to 50 °C; however, increased feed stream velocity also led to increased cake resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Fouling is a limiting phenomenon that can prevent the industrialization of membrane clarification due to increased time and costs (4)(5)(6). Changes in the geometry of the membrane module (e.g.…”
Section: Introductionmentioning
confidence: 99%